The typology of connectivity in landscape architecture: a review of studies on landscape connectivity (LC) - Sazandeh, M.; Faizi, M.; Yazdanfar, S. A.; Behzadfar, M. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Connectivity is an important landscape characteristic that is essential for health, welfare and aesthetic values in human societies as well as for the protection of native ecosystems. Diversity in objectives, approaches, definitions and methods in studies on connectivity and its widespread use in the field of landscape ecology are reasons why Landscape Connectivity (LC) in landscape architecture has been deemed as the counterpart of Ecological Connectivity leading to neglect of other aspects of this comprehensive concept. This study, reviews and classifies studies carried out in the field of landscape with a focus on connectivity in order to achieve a comprehensive definition of LC and its various components in landscape architecture literature. The research method used in this study was quantitative-qualitative. In the first phase, the literature was collected using library research and internet search via a descriptive-analytical approach. Then, an inductive constructionist strategy using Delphi technique was used to classify and categorize relevant studies, and logical argumentation was used to develop the concept of LC in landscape architecture literature. Finally, the objectivist Descriptive/Synthetic Modelling strategy was used to provide a conceptual model of urban landscape connectivity (ULC). The key finding of this study is the researcher-made conceptual model of ULC, its corresponding components and parameters with the viewpoint of landscape architecture.